Integrating Comprehensive Intellectual Capital Management and Social Entrepreneurship : An Interpretive Accounting Research - Sigit Hermawan; Eny Maryanti; Prasetyo Utomo (Jurnal Ilmiah Akuntansi dan Bisnis, 2025)
The substantial potential of zakat, infaq, and sadaqah (ZIS) funds in Indonesia necessitates the involvement of high-performing institutions dedicated to managing these resources, referred to here as amil zakat or ZIS institutions, to ensure their effective utilization. This study seeks to develop a strategic framework for advancing ZIS institutions by leveraging Comprehensive Intellectual Capital Management (CICM) and social entrepreneurship. Data for the study were gathered through in-depth interviews, focus group discussions, documentation, and observation. Findings indicate that ZIS institutions can be strengthened by integrating three key forms of capital: human, structural, and relational. Among these, human capital emerged as the primary driver of institutional development within the Indonesian context. The level of CICM implementation, however, requires alignment with the available resources of each ZIS institution to optimize its impact. Furthermore, social entrepreneurship not only contributes to the development of ZIS institutions but also aligns with the resource-based theory by enhancing institutional adaptability and sustainability. Keywords: comprehensive intellectual capital management, strategic management accounting, social entrepreneurship